THE INFLUENCE OF STRAIN LOCALISATION ON THE ROTATION BEHAVIOUR OF RIGID OBJECTS IN EXPERIMENTAL SHEAR ZONES - ten Grotenhuis S.M.; Passchier C.W.; Bons P.D. (My University, 2002)
Mica fish and tourmaline fish from natural mylonites were analysed in thin section to determine their orientation distribution. They are oriented with their long axes tilted with respect to the mylonitic foliation, and fish with a small aspect ratio exhibit a slightly larger angle than fish with a large aspect ratio. This orientation seems to be a stable orientation for the mica and tourmaline fish. Analogue experiments with two rheologically different matrix materials were performed to explain the data. One material was PDMS, a linear viscous polymer. The other was tapioca pearls, a granular material with low cohesion and Mohr-Coulomb type behaviour. In contrast to a fairly homogeneous strain distribution in PDMS, distinct small-scale shear bands developed in tapioca pearls during deformation. Experiments modelled different vorticity numbers and parallelogram-shaped rigid objects with different aspect ratios were used. Rotation rates of objects in a viscous matrix are very similar to analytical solutions for ellipses in viscous flow, but stable orientations differ from data of natural examples. In all experiments with a Mohr-Coulomb matrix elongated objects had a stable orientation due to small-scale strain localisation. We therefore suggest that small-scale strain localisation (=<mm) that might be hidden by ongoing deformation and recrystallisation processes, is an important characteristic of the rheology of mylonites.
Keywords: STRAIN LOCALISATION; ROTATION BEHAVIOUR; ANALOGUE MODELLING; RHEOLOGY